Analisis Kestabilan Tanah Timbunan (Embankment) Pada Tanah Rawa Dengan Menggunakan Bambu (Studi Kasus : Jalan Toll Manado-Bitung) - Lestari, Mariati Indah; Manoppo, Fabian J.; Rondonuwu, Steeva G. (Sam Ratulangi University, 2018)
Construction of the road structure in the form of embankment on soft ground conditions posesome problems, such as stability, seattlement, horizontal movement (lateral displacement), andcollapse of ground slopes or uneven base decline (differencial seattlement). This is because soft soilsgenerally have strong shear and low permeability and great compressibility. Because the soft soil hasa low permeability, the time required for consolidation is longer. At the time of consolidation, theground stress at the beginning of the loading is borne entirely by the pore-water stress. Then slowlythis stress is transferred to the effective stress of the soil, so that the soil has increased the strength andcarrying capacity. Thus, if a construction is to be built on soft soil, in order to avoid a substantialsettlement in the building and to obtain a good carrying capacity of the soil, the construction processshould be carried out after the soil has been fully consolidated. In this study it will be on the analyzethe stability problems on embankment on soft soil by using bamboo as micropile with case studiesmarshland improvement efforts to heap on it on a toll road project Manado Bitung in North Sulawesi.Â Â Â Â Â Â The aims of this study are to obtain a graphic relationship between safety factor value andengineering properties of soil (c, Ï†, Î³) and to obtain a graphic relationship between safety factor valueand itâ€™s Î±Â Â value.Â Â Â Â Â Methods used in this study are laboratory scale experiment using bamboo as micropile to simulatethe soil stability and rockscience program forn slope stability analysis.Â Â Â Â Â Results revealed that based on the analysis results of construction of embankment without bambooas micro pile and construction of embankment with bamboo as micro pile, it can be concluded thatÂ asswamp land has low carrying capacity and generally have high water content and very lowpermeability so often cause problems inside construction of civil buildings. A common problem withsoft soil is the problem of stability. The result of the analysis, showed that other data (ï¦ , Î³, c, h,) ifthe value of ï¦Â increase then the safety factor will increase, also if the value of c increase then thesafety factorÂ will increase, but if the value of Î³ is decrease then the safety factor will decrease. Byraising the h embankment height, will reduce the safety factor value.Keywords: slope stability, geological process, landslides, Rocscience slide program, safety factor